Health related quality of life and academic achievement in children with epilepsy / Wo Su Woan - Wo, Su Woan (2018)
Epilepsy has a negative pervasive impact in the health related quality of life (HRQOL) of children with epilepsy (CWE) and their parents. Hence, the overall aim of this study was to explore the needs and challenges encountered by parents and their CWE, and to systematically review the impact of epilepsy on a child’s academic achievement. This study was divided into four phases: (1) the validation of the Malay and Chinese parent proxy and child self-report of the HRQOL measure for children with epilepsy (CHEQOL-25), (2) the validation of the Malay and Chinese general functioning subscale (GF-12), (3) the systematic review on the impact of epilepsy on academic achievement in children, (4) the needs and challenges of parents and their children in childhood epilepsy care. In phase 1 and 2, the Malay and Chinese versions of the CHEQOL-25 and GF-12 subscale were validated. These instruments were found to be valid and reliable to assess the HRQOL and family functioning of parents and their CWE in Malaysia, respectively. In phase 3, a search was conducted on five databases for articles published in English from 1980 till March 2015. Included were studies who recruited children (aged 5-18 years), with a diagnosis or newly/recurrent epilepsy, an intelligent quotient (IQ) of ≥70 or attending regular school, with or without a control group, and studies which measured academic achievement using a standardised objective measure. Excluded were children with learning difficulties, intellectual disabilities (IQ<70) and other comorbidities such as attention deficits hyperactive disorder or autism. Twenty studies were included. The majority of the studies assessed “low achievement” whilst only two studies used the IQ-achievement discrepancy definition of “underachievement”. Fourteen studies (70%) reported that CWE had significantly lower academic achievement scores compared to iv healthy controls, children with asthma or reported norms. The remaining six studies (30%) did not report any differences. CWE had stable academic achievement scores over time (2-4 years), even among those whose seizure frequency improved. Higher parental education and children with higher IQ, or had better attention or had a positive attitude towards epilepsy, were associated with higher academic achievement score. Older children were found to have lower academic achievement score. This systematic review highlights the need for early screening of learning problems and continued surveillance. In phase 4, purposive sampling was used to recruit CWE that were attending normal school and their parents. In-depth interviews were conducted in 18 parents (12 caregivers plus 3 pairs of caregivers) and 15 CWE. The experiences of parents and their child with epilepsy were divided into two time frames: “Experiences during their child’s first seizure” and “Experiences whilst growing up with epilepsy”. Parents’ main concerns and worries were their child’s physical health, psychological and emotional wellbeing, academic achievement and their child’s future. The children’s main concerns were restrictions imposed, their interpersonal relationship with peers, and being independent in the future. Parents reported that they needed epilepsy-related information, continuity of care, and parental support group. However, the children reported that their main need was independence and autonomy.